Educational Model Study to Train and Develop Competitive Workers, Based on Learning Objectives - Darmawi, Ahmad (Advances in Social Sciences Research Journal, 2019)
Although training techniques are just right, learning cannot happen if the experience is not arranged properly. So, when drawing up a program of training and development, a very important set of learning stages during a training program or development and to provide the conditions that will sustain the performance in time. The descriptive method is used to search the fact with proper interpretation prior to implementing training programs, responsibility for learning and support the transfer of new behaviors. The content of the training program should be the same as the purpose of the lesson. Some types of learning objectives are the cognitive knowledge, technical skills or interpersonal, effective results, and ethical behavior